Association between serum vitamin D level and insulin resistance in overweight adolescents - Lando, Fabrício Sbroglio; Vargas, Deisi Maria (O Mundo da Saúde, 2023)
The maintenance of glycemic homeostasis and insulin secretion is considered one of the metabolic effects of vitamin D (VD). Traditionally, obesity is the main cause of insulin resistance (IR) and an important risk factor for VD deficiency. Therefore, adolescents with obesity and VD deficiency may be faced with a doubled risk of developing IR. The objective of this study was to evaluate the association between serum levels of 25-hydroxyvitamin D [25(OH)D] and IR parameters in overweight adolescents. This is an observational study of 42 overweight adolescents followed in a secondary care service. Overweight was defined by the criteria of the World Health Organization and serum levels of 25(OH)D were categorized as normal (≥ 30 ng/mL) and low (< 30 ng/mL) according to the Brazilian Society of Nutrology. In the assessment of IR, the homeostatic model of IR assessment (HOMA-IR), the glucose/insulin ratio and fasting insulinemia were used. The studied group was characterized as being predominantly young adolescents (88.1% between 10 and 14 years old), in puberty (83.5%), and having central obesity (80%), and hypovitaminosis D (85.7%). Adolescents with low VD showed a higher occurrence of IR according to the HOMAR IR index (one-tailed Fisher test, p <0.05), suggesting a relationship between vitamin D status and insulin sensitivity; hence, there was a positive association between low VD and high HOMA-IR.